Area coverage of BINA developed rice, pulse, oilseed and horticultural crop varieties in Bangladesh - Rahman, H M; Sarkar, M M A; Haque, M R; Islam, S (Bangladesh Journal of Nuclear Agriculture, 2025)
The study was conducted to assess the area coverage of BINA developed rice, pulse, oilseed and horticultural crop varieties during 2023-24. Field survey data were collected from 64 districts through concern DAE office. Both tabular and descriptive statistical analyses were used. It was observed that the overall area coverage of BINA developed rice varieties were 9.97%. Among the three seasons; Aus, Aman and Boro the highest area coverage was found in Aman season that was 15.49% followed by Aus 11.15% and Boro 3.12%, respectively. Among the 14 agricultural regions, the highest area coverage of rice was found 16.46% in Jashore region (Reg-13) and the lowest was found 1.09% in Rangamati region (Reg-4). The overall area coverage of BINA developed pulse varieties were 8.85% and among the 14 regions the highest area coverage for pulses was found in Barishal region 55.51% (Reg-6). The overall area coverage of BINA developed oilseed varieties were 22.35% and among the 14 regions the highest area coverage for oilseed was found in Jashore region 12.53% (Reg-13). Among the BINA developed horticultural crop varieties the highest area coverage was found 4.58% for Binalebu-1 followed by Binatomato-10 (0.36%) and Binahalud-1 (0.31%). It was also observed that, among the 14 regions the highest area coverage for Binalebu-1 and Binahalud-1 were found in Rangamati region (Region-4) about 495 ha (49.48%) and 117 ha (0.65%), respectively. The study identified that the overall area coverage of BINA developed rice, pulse and oilseed crops for distributed seed were 1%, 1.55% and 4.29%, respectively. The study also observed some constraints such as non-availability of seed, lack of training, demonstrations, field day, collaboration etc. For continuation of variety expansion, the institute should ensure quality seed supply in proper time and training, demonstration as well as collaboration among other organizations such as, DAE, BADC and NGOs should be emphasized. Bangladesh J. Nuclear Agric, 38(2): 97-110, 2024